Perspectives sur l'histoire du karaïsme = Perspectives on the History of Karaism - Dye, Guillaume (PHR series, 2022)
This book examines the history of Karaism, a Jewish religious movement that emerged in the ninth century in Iraq and Palestine, in opposition to rabbinic Judaism and the notion of the Oral Torah. This important current of medieval Judaism, of which a few communities remain today, is a remarkable example of the complexity and variety of Judaism. Cet ouvrage étudie l'histoire du karaïsme, un mouvement religieux juif, apparu au ixe siècle, en Iraq et en Palestine, qui s'oppose au judaïsme rabbinique et à la notion de Torah orale. Ce courant important du judaïsme médiéval, dont il reste quelques communautés aujourd'hui, est un exemple remarquable de la complexité et de la variété du judaïsme.